2016
DOI: 10.1007/s00216-016-0137-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive two-dimensional gas chromatographic profiling and chemometric interpretation of the volatile profiles of sweat in knit fabrics

Abstract: Human axillary sweat is a poorly explored biofluid within the context of metabolomics when compared to other fluids such as blood and urine. In this paper, we explore the volatile organic compounds emitted from two different types of fabric samples (cotton and polyester) which had been worn repeatedly during exercise by participants. Headspace solid-phase microextraction (SPME) and comprehensive two-dimensional gas chromatography time-of-flight mass spectrometry (GC×GC-TOFMS) were employed to profile the (semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…McQueen et al (2014) found higher concentrations of carboxylic acids in the headspace above polyester fabric when compared to cotton fabric after wear. In subsequent analysis of the same fabrics, de la Mata, McQueen, Nam, and Harynuk (2017) were able to distinguish between cotton and polyester fabrics based on their selective sorption of semivolatile compounds. In a study on the profiles of volatiles released in the headspace from four different fabrics (cotton, polyester, wool, and rayon), Prada, Curran, and Furton (2011) noted that the different fabrics selectively retained and released compounds based on various chemical classes.…”
Section: Introductionmentioning
confidence: 99%
“…McQueen et al (2014) found higher concentrations of carboxylic acids in the headspace above polyester fabric when compared to cotton fabric after wear. In subsequent analysis of the same fabrics, de la Mata, McQueen, Nam, and Harynuk (2017) were able to distinguish between cotton and polyester fabrics based on their selective sorption of semivolatile compounds. In a study on the profiles of volatiles released in the headspace from four different fabrics (cotton, polyester, wool, and rayon), Prada, Curran, and Furton (2011) noted that the different fabrics selectively retained and released compounds based on various chemical classes.…”
Section: Introductionmentioning
confidence: 99%
“…7,25 Bisymmetrical T-shirts with a different fabric on each side of the body have been used when multiple wear and wash cycles were needed for odor to develop over time. 26,27 Sweat (predominantly eccrine) was obtained by sewing fabrics to gym mats during circuit training where multiple participants contributed to overall odor. 28 Collection of axillary and upper body sweat was obtained from sampling the whole T-shirt worn by participants after one hour of bicycling spinning exercise.…”
Section: Evaluating Odor On Textilesmentioning
confidence: 99%
“…Volatiles extracted from cotton and polyester fabrics using SPME were analyzed by comprehensive two-dimensional gas chromatography (GC × GC) with time-of-flight mass spectrometry (TOF-MS). 26,27 Two-dimensionality overcomes the problem of peak overlap that can occur in one-dimensional chromatograms of complex mixtures. 73 Between 1000 to 2000 individual compounds were detected, and through advanced chemometric analyses, fabric samples could be clustered by their chemical profile with differentiation between unwashed/washed fabrics, fiber type, and gender of participant.…”
Section: Evaluating Odor On Textilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carboxylic acids, aldehydes, ketones, and alcohols were the classes selected, through application of chemometric algorithms, to distinguish between cotton and polyester textiles. Moreover, aldehydes, alcohols and some aromatics were the most representative to discriminate the sex of the user [143].…”
Section: Biologicsmentioning
confidence: 99%